2017
DOI: 10.1007/s11250-017-1297-5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Brucella antibodies in camels in Katsina State, Nigeria

Abstract: A cross-sectional study was carried out to determine the status of Brucella infection in one-humped (Dromedary) camels in the North and Central senatorial districts of Katsina State, Nigeria. Nine hundred and eighty serum samples from live and slaughtered camels were tested. Modified Rose Bengal plate test (RBPT) and serum agglutination test (SAT) with ethylenediaminetetraacetic acid, (EDTA) were used as screening and standard tests, respectively. The prevalence of Brucella antibodies were 110 (11.2%) and 103 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Since then, it has been testified by all camel rearing countries like Sudan, Ethiopia, Somalia, Kenya, Nigeria, Jordan and Egypt but not Australia [3]. There is no separate specific species of Brucella that displays a preference for camels as they can be infected by those that have already been shown to be prevalent in bovines, ovines and caprines [4][5][6]. The clinical picture of brucellosis in camels can vary from asymptomatic to abortion, retention of fetal membranes, weak offspring, impaired fertility and delayed sexual maturity in females and orchitis accompanied by lameness in males [2,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it has been testified by all camel rearing countries like Sudan, Ethiopia, Somalia, Kenya, Nigeria, Jordan and Egypt but not Australia [3]. There is no separate specific species of Brucella that displays a preference for camels as they can be infected by those that have already been shown to be prevalent in bovines, ovines and caprines [4][5][6]. The clinical picture of brucellosis in camels can vary from asymptomatic to abortion, retention of fetal membranes, weak offspring, impaired fertility and delayed sexual maturity in females and orchitis accompanied by lameness in males [2,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…The primary clinical signs of infection are abortion in females, and orchitis and epididymitis with frequent sterility in males, because of the localization of brucella within the male and female reproductive organs. Large numbers of brucellae can be excreted in fetal fluids and mammary secretions [28,29]. This research work was carried out on A total of 203 (serum -45, placental tissue -40, blood -25, placental fluid -13, milk -50, uterine swab -30) samples of dromedary camels suspected to be or had a history of brucellosis from Qatar.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report discusses 15 camels that were set up to be infected with Brucella in Jordan. 34 Whereas, in another study conducted in Sudan revealed that 40 tested samples were positive for Brucella when 2,000 camel serum and milk samples were examined. 35 Bacterial infections are transmitted to humans from other sources where antibiotics are used for various purposes and should cause emerging resistant strains.…”
Section: Discussionmentioning
confidence: 97%